Development of a versatile nuclease prime editor with upgraded precision - Xiangyang Li; Guiquan Zhang; Shisheng Huang; Yao Liu; Jin Tang; Mingtian Zhong; Xin Wang; Wenjun Sun; Yuan Yao; Quanjiang Ji; Xiaolong Wang; Jianghuai Liu; et al. (Nature Communications, 2023)
Strategies to improve the specificity of nuclease-based prime editor (PEn) are needed. Here the authors report a 53BP1-inhibitory ubiquitin variant-assisted PEn platform (uPEn) to inhibit NHEJ and enable precise prime editing for generation of insertions, deletions and replacements.